Institutions, innovations, and Growth - Xu, Chenggang; Huang, Haizhou (Washington, D.C. : International Monetary Fund, 1999)
The fundamental importance of economic institutions for economic growth through their impact on technological change has been argued, reconfirmed by recent empirical studies, but not examined theoretically. This paper tries to fill that gap. In the model proposed, economic growth is affected by the efficiency and riskiness of research and development (R and D), which are endogenized through financial institutions. The theory and its results shed lights on the debate of convergence versus divergence; the 'East Asia miracle' versus the East Asia financial crisis; and the rise and fall of centralized economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Financial Institution; Macroeconomics; WP